2010
DOI: 10.1029/2010jd014616
|View full text |Cite
|
Sign up to set email alerts
|

Observations of stepping mechanisms in a rocket‐and‐wire triggered lightning flash

Abstract: [1] We present 10 high-speed video images that depict the bottom 150 m of a downwardnegative, dart-stepped leader in a rocket-and-wire triggered flash, recorded at 240 kiloframes per second (4.17 ms frame integration time), along with correlated measurements of the X-ray emission at 50 m, electric field derivative (dE/dt) at 80 m, and the rocketlaunch-tower current beneath the leader. We observed discrete segments of secondary channel that exhibited luminosity above that of the surrounding corona streamers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
118
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(132 citation statements)
references
References 24 publications
13
118
1
Order By: Relevance
“…In their study, disconnected luminous segments interpreted to be space leaders can also be seen to form ahead of the leader tip in the decaying channel remnants. However, Biagi et al [2010] also recorded what appears to be a streamer zone ahead of the dart leader tip, a significant difference from the present study where no such streamer zone was observed.…”
Section: Dart-stepped Leadercontrasting
confidence: 56%
See 3 more Smart Citations
“…In their study, disconnected luminous segments interpreted to be space leaders can also be seen to form ahead of the leader tip in the decaying channel remnants. However, Biagi et al [2010] also recorded what appears to be a streamer zone ahead of the dart leader tip, a significant difference from the present study where no such streamer zone was observed.…”
Section: Dart-stepped Leadercontrasting
confidence: 56%
“…We interpret these segments as analogous to the space leader segments observed during the initial negative stepped leader. The image of the dart-stepped leader also shows a striking lack of an observable corona streamer zone in the volume just ahead of the leader tip, in contrast to the observation by Biagi et al[2010] in which a corona streamer zone can be clearly seen ahead of the tip of a descending dart-stepped leader. Another lower luminosity zone was also observed to extend beyond the low-luminosity breakdown region of the dart-stepped leader tip, a feature that to our knowledge has not been reported in previous literature.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Photographic evidence show that these leaders travel towards ground in intermittent steps and experimental data on the time intervals between the steps and the lengths of the individual steps are available in the literature [1,2]. The available information show that the time interval between steps span from 10 μs to 100 μs and the lengths of the steps span from 5 m to about 200 m [1,2,3,4]. More recently, detailed development of the stepping process in negative lightning leaders has been observed using high speed photography [4].…”
Section: Introductionmentioning
confidence: 99%